2016
DOI: 10.12890/2016_000472
|View full text |Cite
|
Sign up to set email alerts
|

Acute Cholecystitis as a Complication After Colonoscopy: A Case Report and Literature Review

Abstract: Acute cholecystitis after colonoscopy is a rare event, with less than 10 cases described in the literature. We report the case of a male patient with silent gallstones who underwent colonoscopy for follow-up of his Crohn's disease. The colonoscopy revealed erosions in the terminal ileum, from which biopsies were taken. A sessile polyp 4 mm in diameter at the recto-sigmoid junction was also removed. Less than 24 h after the colonoscopy, the patient complained of upper right quadrant pain, nausea and vomiting. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…This episode was registered as a grade 3 adverse event unlikely related to the probiotic intervention, but possibly related to the colonoscopy procedure. Cholecystitis has previously been reported after colonoscopy, but in a shorter time interval after the procedure, and no causality has been established (353,354).…”
Section: Objective 3 -Effects Of the Probiotic Interventionmentioning
confidence: 96%
“…This episode was registered as a grade 3 adverse event unlikely related to the probiotic intervention, but possibly related to the colonoscopy procedure. Cholecystitis has previously been reported after colonoscopy, but in a shorter time interval after the procedure, and no causality has been established (353,354).…”
Section: Objective 3 -Effects Of the Probiotic Interventionmentioning
confidence: 96%
“…In this study, one participant had an SAE unlikely related to the probiotic intervention, but possibly related to the colonoscopy procedure. 41,42 Our study adds data to evidence that probiotics should be considered safe in INRs.…”
Section: Discussionmentioning
confidence: 77%
“…Post colonoscopy cholecystitis was first reported in 2001 by Milman and Goldenberg in a series of two patients [ 5 ]. After this initial report, an additional seven authors reported cholecystitis after colonoscopy [ 6 - 12 ] in a total of twelve patients (Table 3 ). The precise mechanism leading to cholecystitis after colonoscopy remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…and Enterococcus facecalis in the pericholecystic fluid of their patient with gangrenous cholecystitis. In all remaining cases [ 5 , 6 , 8 - 10 ], the most likely underlying pathophysiology is due to increased lithogenicity of bile, as a direct result of the fasting state and commonly used large volume laxatives consumed for bowel cleansing.…”
Section: Discussionmentioning
confidence: 99%